1997
DOI: 10.2307/2265961
|View full text |Cite
|
Sign up to set email alerts
|

The Stable Nitrogen Isotope Ratio as a Marker of Food-Web Interactions and Fish Migration

Abstract: We used stable nitrogen isotopes to describe the pelagic food-web structure of three coastal Baltic Sea areas, each of which was sampled twice. Two of the areas were influenced by 15 N-rich nutrient discharges from a sewage treatment plant. Analyses were made of particulate organic matter (Ͻ35 m, mainly phytoplankton), zooplankton, mysids (Mysis mixta and M. relicta), sprat (Sprattus sprattus), smelt (Osmerus eperlanus), four size classes of herring (Clupea harengus), and pikeperch (Stizostedion lucioperca). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 32 publications
8
114
1
1
Order By: Relevance
“…Typically, energy is transferred from suspended particulate matter to zooplankton to omnivores in aquatic ecosystems. Consistent with other studies (Hansson et al, 1997;Yang et al, 2012), the Δδ 15 N value was 2.65‰ between suspended particulate matter and zooplankton and 2.66‰ between zooplankton and omnivores, indicating that enrichment of δ 15 N was relatively stable compared with δ 13 C. Average δ 13 C and δ 15 N values for the eight macrophytes in this system were -26.30‰±0.45‰ and 5.64‰±0.37‰, respectively. The δ 13 C and δ 15 N values for the macrophytes and suspended particulate matter were lower than other organisms, the reason was that primary use of the 12 C of phytoplankton and macrophytes during photosynthesis leads to low δ 13 C values in phytoplankton (Leggett et al, 1999).…”
Section: Stable Isotopes In the Rice-crab Systemsupporting
confidence: 90%
“…Typically, energy is transferred from suspended particulate matter to zooplankton to omnivores in aquatic ecosystems. Consistent with other studies (Hansson et al, 1997;Yang et al, 2012), the Δδ 15 N value was 2.65‰ between suspended particulate matter and zooplankton and 2.66‰ between zooplankton and omnivores, indicating that enrichment of δ 15 N was relatively stable compared with δ 13 C. Average δ 13 C and δ 15 N values for the eight macrophytes in this system were -26.30‰±0.45‰ and 5.64‰±0.37‰, respectively. The δ 13 C and δ 15 N values for the macrophytes and suspended particulate matter were lower than other organisms, the reason was that primary use of the 12 C of phytoplankton and macrophytes during photosynthesis leads to low δ 13 C values in phytoplankton (Leggett et al, 1999).…”
Section: Stable Isotopes In the Rice-crab Systemsupporting
confidence: 90%
“…Laffaille et al (2001) identified the mysid Neomysis integer as a significant part to the diet of 0-group D. labrax in Mont Saint Michel Bay, France. Mysids are a common estuarine inhabitant, and also have a trophicallyenriched d 15 N ratio compared to zooplankton (Hansson et al 1997;Hampel et al 2003). The use of sulphur stable isotopes (d 34 S) in future studies would provide increased detail for food web and spatial variation studies of salt marsh communities, with the ability to distinguish d 34 Senriched phytoplankton sources from d 34 S-depleted C 4 plants, with C 3 plants as intermediates (Peterson and Fry 1987).…”
Section: Fish Isotope Signatures and The Salt Marsh Food Webmentioning
confidence: 99%
“…This may result in separate fish sub-populations along an estuary, with low connectivity within and between different salt marshes and estuaries along the coastline. Previous studies along the coastlines of Sweden, California and Portugal have identified that nekton has a strong relation to the area it occupies at a relatively small spatial scale (Hansson et al 1997;Kwak and Zedler 1997;Vinagre et al 2011). Our study supports this, and the demonstrates the suitability of stable isotopes in tracing organism feeding and fidelity across habitat patches distinguished by differential d 15 N ratios (Herzka et al 2002;Durbec et al 2010).…”
Section: Fidelity Of Fish Sub-populations To Individual Salt Marshesmentioning
confidence: 99%
See 1 more Smart Citation
“…Field studies generally ®nd a carbon enrichment of 0±1& (Peterson and Fry 1987) or 1±2& (e.g., Keough et al 1996) and a d 15 N enrichment of 3±5& for each increase in trophic level because of selective excretion of lighter isotopes (reviewed in Peterson and Fry 1987). Recent studies, however, have shown that 15 N enrichment can be as little as 2±3& (Hansson et al 1997).…”
Section: Chemical Analysesmentioning
confidence: 99%